Spatial variation in the trophic category of fish assemblages in longitudinal stretches in a Neotropical reservoir - Garcia, Thiago Deruza (2023)
The spatial gradients created after the installation of large reservoirs produce a great diversity of biotopes, which affects the distribution and structuring of aquatic communities, mainly fish. Thus, we hypothesized that the fishes living in the lotic stretch (river zone, closest to the natural environment) of the reservoir would have lower overlap and higher niche breadth than fishes living in the lentic stretch. Samples were collected in six sections (lentic and lotic) of the Chavantes Reservoir, middle Paranapanema River. A total of 1478 individuals distributed in 13 species were sampled in both stretches. Many resources were acquired by species, and we observed that nine species present significant differences when comparing the two stretches. Furthermore, only Schizodon nasutus and Steindachnerina insculpta showed interindividual variability. Despite the large number of food items exploited by the species, the vast majority showed preferential consumption for few food resources, evidenced by the low values of trophic niche breadth in both stretches. Furthermore, it was observed a trend towards specialization of all trophic categories indicated that the results found here, combined with a low degree of niche breadth of the species, offer a high trophic food variation among the fish species in the reservoir.